2013
DOI: 10.1155/2013/354507
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Mediastinal Unicentric Castleman’s Disease Using Video-Assisted Thoracoscopic Surgery with Preoperative Embolization

Abstract: Unicentric Castleman's disease is a rare, benign lymphoproliferative disorder that is curable with surgical resection. However, significant bleeding often occurs during surgery because of tumor hypervascularity. We herein present a case of hyaline-vascular-type mediastinal unicentric Castleman's disease, successfully resected using video-assisted thoracoscopic surgery with preoperative embolization. In the present case, tumor hypervascularity and feeding vessels were revealed by computed tomography (CT), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Preoperative evaluation of feeding and draining vessels around lesions is very important since the standard treatment for patients with UCD is complete surgical resection [18, 23]. Preoperative embolotherapy for hypervascular nodal vessels may facilitate uncomplicated surgical resection [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative evaluation of feeding and draining vessels around lesions is very important since the standard treatment for patients with UCD is complete surgical resection [18, 23]. Preoperative embolotherapy for hypervascular nodal vessels may facilitate uncomplicated surgical resection [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in the reported cases, such as estimated blood loss, effect on tumor size, time interval between angioembolization and surgery, postoperative complications, and use of a surgical drain have been reported. Table 1 lists the literature review on the role of preoperative angioembolization in CD [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Walter et al first reported in 1978 a patient treated with arterial embolization as a preoperative adjunct to surgery to limit intraoperative bleeding 9 . Several case reports have described embolization in Castleman disease, usually for mediastinal masses unresectable at diagnosis, and preoperative use of embolization ensured safer surgical resection 10‐21 . Modern angiography equipment and microcatheters make the identification and selection of vessels feeding the tumor possible.…”
Section: Discussionmentioning
confidence: 99%